Identification of stage-regulated and differentiation-enriched transcripts during transformation of the African trypanosome from its bloodstream to procyclic form. - Matthews, K; Gull, K (1998)
Trypanosoma brucei undergoes dramatic stage-specific changes in surface antigen expression, metabolic development, cellular morphogenesis and cell-cycle control. These events can be studied in detail during the transition between the bloodstream stumpy stage and the tsetse fly midgut procyclic form. This differentiation can be induced in vitro, is synchronous in the population and there are abundant markers for stage-regulated and differentiation events. We have used this differentiation system to investigate the role of de novo transcription during different phases of this well-characterised cellular transformation. Our experiments implicate early transcriptional involvement in shedding of the variable surface glycoprotein coat, cell restructuring and cell-cycle re-entry. The synchrony of differentiation has also been exploited to identify transcripts which define distinct regulated processes during this differentiation. The transcripts identified provide good coverage of the different molecular regulation events that accompany this life-cycle transformation. These included a surface antigen gene (encoding procyclin/PARP), a cell cycle regulated component (encoding histone H2B), a homologue of the Leishmania activated protein kinase C receptor (LACK) and a putative gene for sub unit VI of cytochrome c oxidase.